The Tax Treatment of Social Security : Should the exclusion of benefits be eliminated? - Levy, Mickey D. (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1980)
This study examines the tax treatment of social security. Two important questions are addressed: Should social security benefits be taxed, and should employees and the self-employed be permitted to exclude social security taxes in calculating individual income tax liabilities?
Includes bibliographical footnotes.
ne 14/05/2018
Loan
Keywords: Income tax; Social security taxes